1966
DOI: 10.1007/bf02641022
|View full text |Cite
|
Sign up to set email alerts
|

Determination of aflatoxins in individual peanuts and peanut sections

Abstract: Subsamples of a given lot of peanuts may vary greatly in aflatoxin content due to extreme variability in the degree of contamination of individual kernels. A micro method, adapted from the aqueous acetone procedure recently proposed by Pons and Goldblatt for the determination of aflatoxins in cottonseed products, was developed to permit accurate determination of aflatoxins in individual kernels and kernel sections. Use of this procedure permitted the topographic distribution of aflatoxins within single kernels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

1967
1967
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 5 publications
2
37
1
2
Order By: Relevance
“…In the first case, the variance between samples is going to be much lower than in the second case. Such a consideration is consistent with the observations of Cucullu et al (1966) (section 4.1.). If an Operating Characteristic (OC) curve is derived with such a predictive equation of the variance, then for lots with a true variance value less than that predicted, both producer and consumer risks are going to be overestimated.…”
Section: Comparison Of the Two Methods: Theoretical Aspectssupporting
confidence: 83%
See 2 more Smart Citations
“…In the first case, the variance between samples is going to be much lower than in the second case. Such a consideration is consistent with the observations of Cucullu et al (1966) (section 4.1.). If an Operating Characteristic (OC) curve is derived with such a predictive equation of the variance, then for lots with a true variance value less than that predicted, both producer and consumer risks are going to be overestimated.…”
Section: Comparison Of the Two Methods: Theoretical Aspectssupporting
confidence: 83%
“…For instance, Steiner, Brunschweiler, Leimbacher, and Schneider (1992) found that in pistachio nuts, the aflatoxins were located in brown or brown spotted kernels; 99.2% of a sample and 99.8% of another sample remained without aflatoxins after elimination of this fraction. In another publication, the results obtained for peanut samples indicated that those which contain aflatoxins could be roughly divided into two groups (Cucullu, Lee, Mayne, & Goldblatt, 1966). In the first, there was a higher prevalence of contaminated kernels than in the second, but the level of aflatoxins was lower.…”
Section: Variability and Sampling Plansmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies by researchers on a wide variety of agricultural products such as peanuts and shelled corn (Cucullu et al 1977(Cucullu et al , 1986Johansson et al 2000a) indicate that a very small percentage (0.1%) of the kernels in the lot are contaminated and the concentration on a single kernel may be extremely high. Cucullu et al (1986) reported aflatoxin concentrations in excess of 1 000 000 ng g À1 for individual peanut kernels and 5 000 000 ng g À1 for cottonseed. Shotwell et al (1974) reported finding over 400 000 ng g À1 aflatoxin in a corn kernel.…”
mentioning
confidence: 97%
“…The main difficulty in sampling grains for mycotoxins analysis is normally due to the small percentage of contaminated kernels in a lot (8) and to the considerable variation in the amount of toxin in the contaminated kernels. This variation has been demonstrated in peanuts (1), in cottonseed (5) and in corn (9) especially in non-processed grains.…”
Section: Introductionmentioning
confidence: 83%